2022
DOI: 10.1177/21651434221091230
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Transition to College for Twice-Exceptional Students with ASD: Perspectives From College Service Providers

Abstract: Increasing numbers of academically talented students with autism spectrum disorder (ASD) are accessing higher education. This is an underserved, and understudied cohort of students, as their talents can mask their autism, or their autism can mask their talents. We conducted interviews with 11 professionals who support academically talented students with ASD at 10 very competitive 4-year institutions in the United States. Findings highlighted the significant academic and personal strengths that these students b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Similar to previous studies ( 26 , 27 ), our sample reported experiencing significant social and emotional challenges during the transition to college. This reflects the literature findings [e.g., ( 17 , 20 , 24 , 26 )] regarding the importance of providing social supports and opportunities for students with autism in high school. Many of our participants indicated that high school students with ASD should be encouraged to become involved in extracurricular activities so their social world and experiences can be broadened before college and so they can reflect and learn from any negative social situations that they encounter.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar to previous studies ( 26 , 27 ), our sample reported experiencing significant social and emotional challenges during the transition to college. This reflects the literature findings [e.g., ( 17 , 20 , 24 , 26 )] regarding the importance of providing social supports and opportunities for students with autism in high school. Many of our participants indicated that high school students with ASD should be encouraged to become involved in extracurricular activities so their social world and experiences can be broadened before college and so they can reflect and learn from any negative social situations that they encounter.…”
Section: Discussionsupporting
confidence: 86%
“…Few reported that they participated in or receive targeted instruction or exposure to experiences focused on developing independent living or social skills and relations in high school. As a group, our participants had more developed self-determination skills than in previous studies, potentially because they are academically talented or gifted ( 8 , 13 , 17 ). However, the absence of systematic instruction in some academic and social skills highlights a research-to-practice gap as multiple studies have discussed the importance in developing these skills for individuals with ASD ( 17 , 20 , 24 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…(Chown et al, 2018;Accardo et al, 2019b) • Orientation week helpful to make connections and become familiar with space and resources. (Anderson, 2018;Madaus et al, 2022) • Information available online or in recruitment materials (Retherford and Schreiber, 2015;Chown et al, 2018) • Apps as a potential effective and low-cost support (Francis et al, 2018) • Disability services office (Retherford and Schreiber, 2015;Dymond et al, 2017; • Campus guides at beginning of semester (Barnhill, 2016;Chown et al, 2018) • Residential orientation programs/moving in early (Chown et al, 2018;Goddard and Cook, 2022) • Peer mentors (Roberts and Birmingham, 2017;Trevisan et al, 2021) Transition out of PS:…”
Section: Categories Contributors Challengesmentioning
confidence: 99%